BOOK REVIEWS - Lategan, Bernard C. (Scriptura, 1983)
Atheism and Liberation / Antonio Pérez-Exclarín (ed) - Reviewed by: L A BrandtSuffering / Erhard S Gerstenberger & Wolfgang Schrage (ed) - Reviewed by: Theo Badenhorst